Metallic point сontacts formed by physical vapour deposition and chemical vapour deposition: microscopy study and point-contact spectroscopy: Электpонные свойства металлов и сплавов - Gribov, J.; Caro, T. G. M.; Oosterlaken, S.; Radelaar, N. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
We have made an electron-microscopy study of nanoholes in membranes in successive stages of metal deposition using two different techniques: physical vapor deposition (PVD) and chemical vapor deposition (CVD). One-sided PVD (thermal evaporation) of gold and silver was used, as is relevant for heterocontacts. The key results in this case are: 1) the holes are not filled during deposition and 2) closing of the holes is accomplished by lateral growth of the film on the membrane. In the case of CVD of tungsten we found that nanoholes in membranes are filled at the beginning of the deposition, and that the process is capable of filling holes as small as 10 nm. Fabricated devices (alpha-tungsten) show good quality point-contact spectra which are characteristic of ballistic transport through the constriction. A very interesting stepwise current increase was observed for one amorphous tungsten point contact.